Is the addition of a neurokinin-1 receptor antagonist beneficial in moderately emetogenic chemotherapy?: a systematic review and meta-analysis - Jordan, Karin; Müller-Tidow, Carsten (Supportive care in cancer, 2018)
Purpose: This systematic review evaluates the efficacy of neurokinin-1 receptor antagonists (NK1RAs) for the prevention of chemotherapy-induced nausea and vomiting (CINV) in moderately emetogenic chemotherapy (MEC) excluding anthracycline-cyclophosphamide-based regimens. Methods: A systematic review of MEDLINE (via PubMed and OVID) and Central databases, plus major oncology conferences, identified randomized trials evaluating NK1RAs in combination with a 5-HT3 RA plus a glucocorticoid for management of CINV. Efficacy endpoints were complete response (CR), no emesis and no nausea rates. Data were analyzed using a random effects model. Results: Sixteen trials (3848 patients) were identified. Results were separately analyzed for (a) pure MEC regimens (excluding regimens containing carboplatin or oxaliplatin), (b) carboplatin-based regimens, and (c) oxaliplatin-based regimens. (a) Two trials (abstracts) enrolled 715 patients. The odds ratio for overall CR with the addition of an NK1-RA was 1.46 (95% 1.06-2.02; p = 0.02) with an absolute risk difference (RD) of 8%. (b) Nine trials (1790 patients) were identified. The OR for achieving an overall CR was 1.96 (95% CI 1.57-2.45; p < 0.00001) in favor of the NK1RA containing regimen with an RD of 15%. (c) Three trials (1190 patients) were identified. The OR for achieving an overall CR was 1.34 (95% CI 0.88-2.04; p = 0.17) not reaching statistical significance with a RD of 4%. Conclusion: Clear clinically significant benefit was seen with the addition of NK1RAs in carboplatin-based chemotherapy. A global benefit of an NK1RA containing regimen for the whole MEC category cannot be attested yet and warrants more randomized trials exclusively testing pure MEC regimens without carboplatin.
Gesehen am 20.08.2018
Online veröffentlicht: 31. August 2017